Differential Effects on Survival, Humoral Immune Responses and Brain Lesions in Inbred BALB/C, CBA/CA, and C57BL/6 Mice Experimentally Infected with Neospora caninum Tachyzoites. (24th March 2013) - Mols-Vorstermans, Tanja; Hemphill, Andrew; Monney, Thierry; Schaap, Dick; Boerhout, Eveline
Abstract : C57BL/6, BALB/c, and CBA/Ca mouse strains with different MHC-I haplotypes were compared with respect to susceptibility to Neospora caninum infection. Groups of 5 mice received1 × 10 6, 5 × 10 6, or25 × 10 6 tachyzoites of the NC-Liverpool isolate by intraperitoneal injection and were observed for disease symptoms. Humoral responses, splenocyte interferon- γ (IFN- γ ) production, cerebral parasite loads, and histopathology were evaluated at human end points or the latest at 34 days postinfection (PI). The mortality rates in C57BL/6 mice were the highest, and relatively high levels of IgG1 antibodies were detected in those mice surviving till 34 days PI. In lymphocyte proliferation assays, spleen cells from C57BL6 mice stimulated with N. caninum antigen extract exhibited large variations in IFN- γ production. In BALB/c mice mortality was 0% at the lowest and 100% at the highest infection dose. Serologically they responded with high levels of both IgG2a and IgG1 subclasses, and lymphocyte proliferation assays of surviving mice yielded lower IFN- γ levels. CBA/Ca mice were the most resistant, with no animal succumbing to infection at a dose of1 × 10 6 and5 × 10 6 tachyzoites, but 100% mortality at25 × 10 6 tachyzoites. High IgG2a levels as well as increased IFN- γ in lymphocyte proliferation assays were measured in CBA/Ca mice infected with1 × 10 6 tachyzoites.